TRANQUILITY AMONGST CHAOS GREAT MOSQUE OF CIBIRU AT CIBIRU DISTRICT, BANDUNG - Ayu Cahyaningtyas, Mutia
Bandung as the city with the highest index of islamic in Indonesia continues to intensify various government programs related to social and religious development. The emergence of the programs had impacts on the need to provide worship facilities that continue to grow in each sub-district of Bandung, included Cibiru District. The project of Cibiru District Mosque is located at Jalan A.H Nasution No 20 with area 7,700 m2 and was initiated by the Regional Government of Cibiru SubDistrict. Located at the central area of the traffic jam and bustle of the city makes this project need to get special design treatment and settlement. A solution-based design approach results in the basic concept of Tranquility amongst Chaos. This concept illustrates how mosque as worship building must be able to create a peaceful atmosphere that can support worship and prayer activities for users. The building is designed by combining nuances of nature, basic geometric shape of the mass, as well as light-and-shadow effects to create an atmosphere of tranquility, sacred, and monumental of the mosque.